Theatre and Metatheatre Definitions, Problems, Limits - Paillard, Elodie; Milanezi, Silvia (MythosEikonPoiesis, 2021)
In this book, experts discuss the use of 'theatre' and 'metatheatre' to describe ancient Greek dramatic activities. By examining how these two concepts are used in very different ways by scholars of various horizons, this collective volume aims both at widening what should be encompassed under the label 'theatre' when looking at the ancient Greek world and at better defining what could count as 'metatheatre' in ancient Greek dramatic production.